The Influence’s Culture Work on the Work Effectiveness of Employees at the Communication and Informatics Agency Province of West Sumatera - Annisa, Khaira; Frinaldi, Aldri (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2020)
Communication and informatics office of west Sumatra make efforts to increase employees’ working effectiveness in achieving working target. However, there are specific problems in working implementation. The problems are teamwork among the employees, working facilities is not supported, and lack of field specialization. This research use descriptive quantitative method that is aims to know the influence between independent variable (working culture) towards dependent variable (employees’ working effectiveness). The population of this research is employee of Communication and informatics office of west Sumatra that is 47 employees. This research use total sampling which the total sample is equal to total population. The result of this research show significance effect partially and simultaneously between working culture towards employees’ working effectiveness as big as 24,4%.